â€œMerebut Kembali Tanah Leluhurâ€: Dinamika Akses dan Pengelolaan Hutan Masyarakat Adat Marena - Arif Maulana Talitti Mattata (Universitas Muslim Maros, 2023)
The access of the Marena indigenous people in Enrekang Regency, South Sulawesi Province, Indonesia to their land has changed from time to time. Since community land is claimed by the state as state forest areas, community access is limited. When the Marena indigenous people obtained a customary forest decree from the Ministry of Environment and Forestry, community access was regulated through customary control. This article focuses on the dynamics of access for the Marena indigenous people in accessing their land. This qualitative research was conducted in the Marena customary territory. There were 16 informants consisting of traditional leaders, former hamlet heads, head of AMAN, land owners, and the Marena indigenous people who do not own land in the customary forest. Primary data was collected using observation and in-depth interviews, while secondary data from various regulations (i.e. Constitution, Law, Government Regulation, Regional Regulation, District Head Decree, Constitutional Court of Indonesia Decree, etc.) and related publications (books, articles, reports, etc.) were also examined. The results of this study indicate that community access to forests is determined by state policies. In the beginning, the community had free access to their land before their plantations became state forest areas. Changes in the status of community land to state forest areas, limiting community access to their land so that the Marena indigenous people have to make some efforts, namely mediation, uprooting poultices, logging clandestinely and openly, poisoning pine trees, and expelling rude forest rangers. Changes in forestry policy after the Orde Baru era marked the era of recognition of forest management by indigenous peoples. This is used by the people in Marena's customary territory to free up their land which was previously made into state forest. For that, they are assisted by AMAN and the local government. AMAN played a role in facilitating the Marena indigenous people in legalizing their customary forest. The Enrekang Regional Government played a role in issuing the Enrekang Regency Regional Regulation No. 1 of 2016 concerning Recognition and Protection of Indigenous Peoples in Enrekang Regency and District Head Decree No. 155/KEP/II/2018 concerning Recognition of Marena Customary Law in Enrekang District recognition of customary forests. The government of Pekalobean and Singki villages played a role by giving approval for Marena's customary territory. It is undeniable that the involvement of these institutions have an important role in their land acquisition. In addition, the boundaries of customary forest areas are quite dynamic. Customary forest is a mechanism to protect community land, so that they can access their land and take advantage of natural resources in customary forests. However, customary rules need to be updated, so that they are relevant to today's context. In addition, the management of resources in the form of pine can be exploited for its economic potential by utilizing pine sap and making it a tourist attraction. Recognition of indigenous peoples needs to be tightened because it is political to reclaim access to natural resources.